Neighbourhood environment and physical activity in older adults. (January 2016) - Chaudhury, Habib; Campo, Michael; Michael, Yvonne; Mahmood, Atiya
Abstract: Rationale: The neighbourhood socio-physical environment has effects on health in later life including health behaviours, chronic illnesses, mental health and mortality. Few studies have examined the relationship of both physical environmental features and social aspects of neighbourhood with older adults' physical activity. Objective: This study examined the relationship of neighbourhood physical and social environment with physical activity among older adults. Methods: A cross-sectional telephone survey was conducted with 434 older adults in eight neighbourhoods in greater Vancouver, Canada and Portland, United States. Data included participants' perceptions of their neighbourhood built and social environment factors and levels of physical activity. A logistic regression analysis was conducted to understand the relationship between these factors. Results: Participants engaged in physical activity most frequently at home (87.1%) or in close proximity of home (76.5%). Neighbourhood walkability, presence of amenities and accessibility were not significantly associated with meeting physical activity requirements. Participation in a recreational program with friends was associated with increased likelihood of physical activity. Conclusion: The home and its immediate physical environmental context has potentially important relevance in supporting physical activity in older adults. Also, neighbourhood social aspects have a positive influence on activity levels. Highlights: A survey was conducted with 434 older adults in eight neighbourhoods. Walkability, amenities and accessibility were not significantly associated with physical activity. Recreational physical activity was more likely to occur when it takes place with friends. Neighbourhood area close to home is potentially important for physical activity.